Kontribusi Badri Yatim dalam Historiografi Islam - Bilal Hardiansyah; Zaenal Abidin; Muhamad Shoheh (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2018)
History is past responsibility. In essence history cannot be separated from human life as the most perfect living creature in form and behavior. Writing history is an attempt to reconstruct events that happened in the past. In the development of Indonesian historiography there are several historiographic features, namely traditional historiography and modern historiography. One historian who is consistent in writing the history of the development of Islam is Badri Yatim. According to Badri Yatim, the style of historical writing in historical works can be grouped into khabar patterns, hawliyat patterns and mawadhu'iyat patterns. The formulation of the problem in this research are: 1. What is the biography of Badri Yatim? 2. What is the theoretical study of historiography? 3. What is the contribution of Badri Yatim in Islamic historiography? This study aims to find out: 1. Biography of Badri Orphans. 2. Theoretical historiography study. 3. Contribution of Badri Yatim in Islamic historiography. This study uses historical research methods which include the following stages: Topic selection, heuristics, criticism, interpretation and historiography. This study concluded that: Badri Yatim was born in Curup (Bengkulu) in 1957, from husband and wife Muhammad Yatim and Nurdinah. Badri Yatim was married to Eli Nurmali in 1987. In the narrative of history there was always found a writer 's partiality for the benefit of certain individuals or groups. Historiography serves to document and explain facts and data regarding events or events in the past. Islamic historiography aims to show the development of historical concepts both in thought and in the scientific approach that is carried out accompanied by a description of the growth, development and decline of the forms of expression used in the presentation of historical materials. The writing style of Badri Yatim uses the narrative method by presenting an event or event based on the time sequence. Badri Orphan is objective in describing and explaining clearly using easy-to-understand language with a clear path.